An aptamer-binding DNA walking machine for sensitive electrochemiluminescence detection of tumor exosomes. Issue 2 (6th December 2019) - Feng, Qiu-Mei; Ma, Po; Cao, Qi-Hang; Guo, Yue-Hua; Xu, Jing-Juan
Abstract : An aptamer-binding DNA walking machine is reported for sensitive electrochemiluminescence (ECL) detection of tumor exosomes. Abstract : An aptamer-binding DNA walking machine triggered by the recognition of aptamers to exosomes was firstly reported for sensitive electrochemiluminescence (ECL) detection of exosomes.